Fertility-sparing Surgery (FSS) in Epithelial Ovarian Cancer (EOC): A Case Report - Khatun, Shahla; Deeba, Farzana; Alam, ABM Muksudul; Ivy, Roksana; Parveen, Farhana (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Epithelial ovarian cancer is the most common and lethal ovarian cancer. Now a days Fertility preservation is an important issue because of the constant shifting of childbearing age towards higher ages. The increasing incidence of epithelial ovarian cancer in women with active childbearing potential constitutes a therapeutic dilemma. Fertility sparing techniques are being increasingly incorporated in the therapeutic strategies in early stages of the disease. Established organ-preserving techniques in early stage epithelial ovarian cancer includes preservation of the contralateral ovary and uterus. Aim: To report the case of a Epithelial Ovarian Cancer, who had conservative surgery followed by chemotherapy with a good fertility outcome. Case presentation: A 31-year-old nulliparous woman with a right sided ovarian mucinous cystadenocarcinoma was treated by right adnexectomy and omentectomy followed by chemotherapy. A 3years follow-up showed no signs of relapse, and she completed a fullterm natural pregnancy which was delivered by caesarean section. Conclusion: Fertility sparing surgery in early stage Epithelial Ovarian Cancer has good prognosis. However, due to the rarity of the disease in early stages, the fertility outcome of this group of patients has not been established. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(1): 46-48